Antibodies against the Majority Subunit (PilA) of the Type IV Pilus of Nontypeable Haemophilus influenzae Disperse Moraxella catarrhalis from a Dual-Species Biofilm - Mokrzan, Elaine M. (mBio, 2018)
Otitis media (OM) is often polymicrobial, with nontypeable Haemophilus influenzae (NTHI) and Moraxella catarrhalis (Mcat) frequently cocultured from clinical specimens. Bacterial biofilms in the middle ear contribute to the chronicity and recurrence of OM; therefore, strategies to disrupt biofilms are needed. We have focused our vaccine development efforts on the majority subunit of NTHI type IV pili, PilA. Antibodies against a recombinant, soluble form of PilA (rsPilA) both disrupt and prevent the formation of NTHI biofilms in vitro. Moreover, immunization with rsPilA prevents and resolves NTHI-induced experimental OM. Here, we show that antibodies against rsPilA also prevent and disrupt polymicrobial biofilms. Dual-species biofilms formed by NTHI and Mcat at temperatures that mimic the human nasopharynx (34°C) or middle ear (37°C) were exposed to antiserum against either rsPilA or the OMP P5 adhesin of NTHI. NTHI+Mcat biofilm formation was significantly inhibited by antiserum directed against both adhesin proteins at either temperature. However, only anti-rsPilA disrupted NTHI+Mcat preestablished biofilms at either temperature and actively dispersed both NTHI and Mcat via interspecies quorum signaling. Newly released NTHI and Mcat were significantly more susceptible to killing by antibiotics. Taken together, these results revealed new opportunities for treatment of biofilm-associated diseases via a strategy that combines vaccine-induced antibody-mediated biofilm dispersal with traditional antibiotics, at a significantly reduced dosage to exploit the newly released, antibiotic-sensitive phenotype. Combined, our data strongly support the utility of rsPilA both as a preventative and as a therapeutic vaccine antigen for polymicrobial OM due to NTHI and Mcat.